Lab-on-chip, internet of things, analytics and health care 4.0: a synergistic future forward - Narayanamurthy, Vigneswaran; K.S., Bhuvaneshwari; Z.E., Jeroish; Fahmi, Samsuri (IOP Publishing, 2020)
In this era of the internet with the latest technology and rapid communication, the various fields of processes and business are led to the road of automation in recent days. The major part of this automation is that they help in the cost reduction with increased safety measures and also results in absolute portability of the equipment. To indulge in continuous processing, and also to identify the best technology, the analytical methods must be directly involved in decision making. This revolution in analytical methods is named as Analytics 4.0, which has a significant role in healthcare and diagnostics. The self-assessment and decentralization of the data acquiring can be motivated with the help of the microfluidic biosensors and biochip. It also helps in the immediate access of the information without resulting in delay. Diagnostic 4.0 helps in storing the patient details as cloud files providing high security and also analyze them through the deep learning algorithms. It also helps in constant monitoring on a broad scale and reliable assessment through monitoring apps that can shift the health care efficiency to the next notch. Hence the evolution of the healthcare sector has multiple generations listed with numerous advances which stand as the boon in this era.